Dose-Limiting Organs at Risk in Carbon Ion Re-Irradiation of Head and Neck Malignancies: An Individual Risk-Benefit Tradeoff - Held, Thomas (Cancers (Basel), 2019)
Background: Carbon ion re-irradiation (CIR) was evaluated to investigate treatment planning and the consequences of individual risk-benefit evaluations concerning dose-limiting organs at risk (OAR). Methods: A total of 115 consecutive patients with recurrent head and neck cancer (HNC) were analyzed after initial radiotherapy and CIR at the same anatomical site. Toxicities were evaluated in line with the Common Terminology Criteria for Adverse Events 4.03. Results: The median maximum cumulative equivalent doses applied in fractions of 2 Gy (EQD2) to the brainstem, optic chiasm, ipsilateral optic nerve, and spinal cord were 56.8 Gy (range 0.94–103.9), 51.4 Gy (range 0–120.3 Gy), 63.6 Gy (range 0–146.1 Gy), and 28.8 Gy (range 0.2–87.7 Gy). The median follow up after CIR was 24.0 months (range 2.5–72.0 months). The cumulative rates of acute and late severe (≥grade III) side effects after CIR were 1.8% and 14.3%. Conclusion: In recurrent HNC, an individual risk-benefit tradeoff is frequently inevitable due to unfavorable location of tumors in close proximity to vital OAR. There are uncertainties about the dose tolerance of OAR after CIR, which warrant increased awareness about the potential treatment toxicity and further studies on heavy ion re-irradiation.